2020
DOI: 10.1136/bjophthalmol-2019-315579
|View full text |Cite
|
Sign up to set email alerts
|

Intraoperative iatrogenic retinal breaks in 23-gauge vitrectomy for stage 3 and stage 4 idiopathic macular holes

Abstract: AimsTo investigate characteristics of intraoperative iatrogenic retinal breaks in 23-gauge vitrectomy for idiopathic macular hole and classify the breaks based on their causes to analyse the risk factors.MethodsThis retrospective study enrolled patients with stage 3 or 4 idiopathic macular hole who underwent 23-gauge vitrectomy in Beijing Tongren Hospital from July 2015 to August 2018. The intraoperative iatrogenic retinal breaks were classified into three types: by induction of posterior vitreous detachment (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 16 publications
0
4
0
1
Order By: Relevance
“…The fluttering of retina was much less than PFCL assisted vitrectomy alone. This allows much safer peripheral vitreous cutting, another main cause for iatrogenic break [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The fluttering of retina was much less than PFCL assisted vitrectomy alone. This allows much safer peripheral vitreous cutting, another main cause for iatrogenic break [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that induction of posterior vitreous detachment lead to 50% of all iatrogenic retinal tear [13] and risk of developing iatrogenic break seemed to be correlated to adhesion of the posterior vitreous hyaloid [14,15]. While in pathological myopic patients, the surgical induction of PVD was more difficult with residual vitreous cortex more often presented [16], possibly due to the adhesion caused by presence of proinflammatory and angiogenesis-related cytokines in their vitreous [17].…”
Section: Discussionmentioning
confidence: 99%
“…The iatrogenic retinal tear rate during vitrectomy has decreased from as high as 37% in the 1970ʹs, 34 to 2–7% today. 33 , 35 , 36 Using the technological innovations of small gauge, cannulated entry, 37 , 38 and the ultra-high-speed suction/cutters recently developed by outstanding corporate partners in the vitreoretinal surgery industry, my experience is that the iatrogenic tear rate can now be further reduced to less than 1%, using VOV techniques.…”
Section: Discussionmentioning
confidence: 99%
“…In our case series, scleral-depressed peripheral examinations were performed at the end of each surgery and no retinal break was identified in each case at the end of the procedure. As reported, the incidence of retinal breaks of macular diseases such as epiretinal membrane (ERM) and MH was low, ranging from 0 to 15.8% [23][24][25][26][27][28][29], but with an average of less than 2.0% [23][24][25][26][27]. The 0% rate of complications in our technique may be owing to the nonscleral-depressed shaving of the vitreous base, vitrectomy by only one experienced surgeon (P.X), and the relatively small sample size.…”
Section: Discussionmentioning
confidence: 99%